Neutrophil extracellular trap formation and extracellular DNA in sputum of stable COPD patients. Issue 10 (October 2015) - Pedersen, Frauke; Marwitz, Sebastian; Holz, Olaf; Kirsten, Anne; Bahmer, Thomas; Waschki, Benjamin; Magnussen, Helgo; Rabe, Klaus F.; Goldmann, Torsten; Uddin, Mohib; Watz, Henrik
Abstract: Introduction: Chronic obstructive pulmonary disease (COPD) is characterized by neutrophilic airway inflammation. Neutrophil extracellular trap (NET) formation – a meshwork of neutrophil DNA components and neutrophil enzymes are involved in innate immunity and inflammation. Little is known about the presence of these structures in induced sputum from stable COPD patients. Methods: Induced sputum samples of 23 COPD patients and 10 healthy controls were collected. Sputum cells were harvested, cultivated and stained for NET components. Extracellular DNA was quantified using a NanoDrop 2000 spectrophotometer. Results: NET formation was markedly upregulated in COPD sputum compared with healthy controls, irrespective of sputum purulence or smoking status. NET formation was associated with significantly higher concentration of extracellular DNA in sputum supernatant (484 ng/μl in COPD versus 268 ng/μl in controls, p = 0.013). Log-transformed extracellular DNA correlated with log-transformed absolute neutrophil numbers in sputum (r = 0.60; p < 0.001) and airway obstruction (r = −0.43; p = 0.013). Conclusion: NET formation associated with higher concentrations of extracellular DNA may be a pathobiological feature of COPD-derived sputum neutrophils. Highlights: Stable COPD patients show enhanced NET formation and extracellular DNA in sputum. No difference in NET formation between ex-smokers and current smokers with COPD. No difference in NET formation between non-purulent and purulent sputum in COPD. Correlation of extracellular DNA with sputum neutrophil numbers and lung function.